2017
DOI: 10.1111/etap.12246
|View full text |Cite
|
Sign up to set email alerts
|

Why is Family Firms’ Internationalization Unique? A Meta–Analysis

Abstract: Despite its importance, there is no clear understanding of the uniqueness of family firms’ internationalization. This article sheds new light on this issue with a meta–analysis of 76 studies covering 41 countries. We show that the considerable study and cross–country differences in the relationship between family firm and internationalization are explained by the roles of family control, internationalization types, and home countries’ institutional contexts (i.e., minority shareholders protection and generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
294
0
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 252 publications
(315 citation statements)
references
References 116 publications
(187 reference statements)
15
294
0
6
Order By: Relevance
“…Our results suggest that family‐managed firms are more averse to internationalization than family firms managed by nonfamily professionals. The results are consistent not only with our theoretical predictions, but also with prior studies in other contexts (Arregle et al, ) that have reported that a significant family presence in both ownership and top management leads to lower internationalization in terms of both scale and scope and internationalization strategies are more successful when the CEO is a nonfamily member (Banalieva & Eddleston, ). Earlier studies identify other factors that make family managers more risk averse (Graves & Thomas, ) and focused on stability (Lee, ), thus discouraging growth strategies like internationalization (Fernández & Nieto, ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that family‐managed firms are more averse to internationalization than family firms managed by nonfamily professionals. The results are consistent not only with our theoretical predictions, but also with prior studies in other contexts (Arregle et al, ) that have reported that a significant family presence in both ownership and top management leads to lower internationalization in terms of both scale and scope and internationalization strategies are more successful when the CEO is a nonfamily member (Banalieva & Eddleston, ). Earlier studies identify other factors that make family managers more risk averse (Graves & Thomas, ) and focused on stability (Lee, ), thus discouraging growth strategies like internationalization (Fernández & Nieto, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, multidimensional measurement approaches are still limited (Verbeke, Li, & Goerzen, ), especially in studies on family firms (e.g., Arregle, Naldi, Nordqvist, & Hitt, ; Arregle et al, ; Pukall & Calabrò, ; Zahra, ). The lack of consistency in operationalization may explain to some extent the inconsistent results in regard to whether family firms are more or less likely to internationalize than nonfamily firms (Arregle et al, ). Therefore, we answer calls in the family firm literature to include multiple dimensions of internationalization (Arregle et al, ; Banalieva & Eddleston, ; Pukall & Calabrò, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…According to this view, conflicts of interests arise in family firms between majority and minority shareholders. As Arregle, Duran, Hitt, and Van Essen (2017) point out, the agency conflict between family and nonfamily shareholders-a conflict principal to principal-is most common in family firms; the reason proposed by Singla, Veliyath, and George (2014) responds to the fact that family managers can take decisions that benefit their family instead of all the shareholders. In this vein, Morck, Wolfenzon, and Yeung (2005) owner, it is expectedly elevated and problematic costs for outside investors.…”
Section: The Moderation Effect Of Family Ownershipmentioning
confidence: 99%